2021
DOI: 10.18069/firatsbed.823831
|View full text |Cite
|
Sign up to set email alerts
|

Güncellenen 2018 Fen Bi̇li̇mleri̇ Öğreti̇m Programina İli̇şki̇n Fen Bi̇li̇mleri̇ Öğretmenleri̇ni̇n Görüşleri̇: Malatya Ve Di̇yarbakir Örneği̇

Abstract: 2018 fen bilimleri dersi öğretim programı, durum çalışması, öğretmen görüşleri ÖZ Bu çalışmada 2017 yılında yenilenen ve 2018-2019 eğitim öğretim yılında güncellenerek ortaokulların her kademesinde uygulamaya konulan 2018 fen bilimleri dersi öğretim programı hakkında fen bilimleri öğretmenlerinin görüşlerini belirlemek amaçlanmıştır. Araştırmada nitel araştırma yöntemlerinden biri olan durum çalışması kullanılmıştır. Araştırma, 2019-2020 eğitim öğretim yılında Malatya ve Diyarbakır illerinde bulanan ortaokulla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…When the opinions of the teachers were examined, it was concluded that despite the simplification of the content, the subjects are not evenly distributed across the grade levels. Similar results were also found in the study of Karabulut et al (2021). Duzgunoglu and Ozcan (2017) also found that the distribution of the subjects across the grade levels is not balanced.…”
Section: Discussion Results and Suggestionssupporting
confidence: 81%
See 3 more Smart Citations
“…When the opinions of the teachers were examined, it was concluded that despite the simplification of the content, the subjects are not evenly distributed across the grade levels. Similar results were also found in the study of Karabulut et al (2021). Duzgunoglu and Ozcan (2017) also found that the distribution of the subjects across the grade levels is not balanced.…”
Section: Discussion Results and Suggestionssupporting
confidence: 81%
“…However, during the teaching of these subjects, problems are experienced due to the fact that the subjects are placed at the end of the units, the weekly class hours are not sufficient and the required materials cannot be provided. Some of the teachers who participated in the study conducted by Karabulut, Koca and Türkoğlu (2021) stated that the subjects cannot be fully covered due to insufficient class hours, crowded classes and high number of activities. The teachers participating in the current study also stated that they have to focus on solving questions in the class because the system is exam-oriented and parents prioritize academic achievement.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
See 2 more Smart Citations